Light impurity transport in JET ILW L-mode plasmas. (18th January 2018) - Bonanomi, N.; Mantica, P.; Giroud, C.; Angioni, C.; Manas, P.; Menmuir, S.
Abstract: A series of experimental observations of light impurity profiles was carried out in JET (Joint European Torus) ITER-like wall (ILW) L-mode plasmas in order to investigate their transport mechanisms. These discharges feature the presence of 3 He, Be, C, N, Ne, whose profiles measured by active Charge Exchange diagnostics are compared with quasi-linear and non-linear gyro-kinetic simulations. The peaking of 3 He density follows the electron density peaking, Be and Ne are also peaked, while the density profiles of C and N are flat in the mid plasma region. Gyro-kinetic simulations predict peaked density profiles for all the light impurities studied and at all the radial positions considered, and fail predicting the flat or hollow profiles observed for C and N at mid radius in our cases.